2005
DOI: 10.1007/s11136-005-8028-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Sociodemographic Factors, Clinical Conditions, and Health-related Quality of Life: Examining the EQ-5D in the U.S. General Population

Abstract: In the U.S., sociodemographic factors and clinical conditions are strongly associated with scores on the EQ-5D. Population health studies and risk-adjustment models should account and adjust for these factors when assessing the performance of health programs and clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

43
167
4
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(226 citation statements)
references
References 38 publications
43
167
4
10
Order By: Relevance
“…Therefore, one needs to be cautious when making international comparisons of population health status. A large ceiling effect (a large proportion of the population tending to report good health, which here refers to reporting no problems in any EQ-5D dimensions) as found in our study (87%) has also been observed in other studies including Chinese populations, in China (Wang et al, 2005), as well as in US (Fu & Kattan, 2006;Lubetkin et al, 2005) and Canada (Leung et al, 2007). This was also the case in a study in Japan (Tsuchiya et al, 2002) and in Malaysia (Shafie et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, one needs to be cautious when making international comparisons of population health status. A large ceiling effect (a large proportion of the population tending to report good health, which here refers to reporting no problems in any EQ-5D dimensions) as found in our study (87%) has also been observed in other studies including Chinese populations, in China (Wang et al, 2005), as well as in US (Fu & Kattan, 2006;Lubetkin et al, 2005) and Canada (Leung et al, 2007). This was also the case in a study in Japan (Tsuchiya et al, 2002) and in Malaysia (Shafie et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Comparison of our results with population studies in other countries showed similar findings, with most problems reported in the pain/discomfort dimension, followed by the anxiety/depression dimension, more problems with increased age and women reporting worse health than men (Burström et al, 2001;Kind et al, 1998;König et al, 2009;Leung et al, 2007;Lubetkin et al, 2005;Sun et al, 2010;Sorensen et al, 2009;Szende & Williams, 2004;).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“….' Last but not least, our study sample seems to be an exceedingly positive group that does well, because their HRQoL was almost one-fifth higher than the HRQoL measured in other stroke study populations [29][30][31][32]. It is not simply that the participants had a relatively high HRQoL, it seems also that there might be another explanatory variable for their HRQoL than functional status, as both LH and EH participants had about the same HRQoL at 3 months, despite the LH participants were more severely disabled.…”
Section: Discussionmentioning
confidence: 74%
“…Although HRQOL involves a lack of conceptual clarity and measurement feasibility [21,22], epidemiological studies have widely recognized HRQOL measurement as a consideration of disease stage or treatment/intervention effects in patients and as a determinants of disparity in specific conditions (i.e., socioeconomic status, employment, and disease prevalence) in the general population [23][24][25][26][27][28]. As applied to current study, the EQ-5D applied to the current study is a valid generic instrument for health status that captures health in terms of mobility, self-care, usual activities, pain/discomfort, and anxiety/depression.…”
Section: Discussionmentioning
confidence: 99%